Unraveling the Mechanisms of the Apis mellifera Honeycomb Construction by 4D X-ray Microscopy - Franklin, Rahul (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 The Authors. Advanced Materials published by Wiley-VCH GmbH.